Exploring three dimensional culture system for cartilage tissue engineering application: a review - Abdul Rahman, Rozlin; Mohamad Sukri, Norhamiza; Md Nazir, Noorhidayah; Ahmad Radzi, Muhammad Aa'zamuddin; Mohamad, Mohd Yusof; Sha'ban, Munirah (2014)
Articular cartilage is a unique tissue with limited self-repair ability. The field of articular cartilage tissue engineering has emerged as a significant complementary solution that involves multidisciplinary field and refers to the practice of combining scaffolds, cells, and signalling molecules into functional tissues. The main goal of tissue engineering is to assemble functional constructs or human spare parts that are able to repair, restore, maintain, or improve damaged tissues or whole organs. In mimicking the in vivo microenvironment to resemble physiological conditions, both conventional two-dimensional (2D) and three-dimensional (3D) biomaterial based culture are important in a wide range of cartilage research. Two dimension cell culture techniques have been developed for decades and have become the standard technique of cell culturing across the globe. In the absence of systematic variations from in vivo system, 2D cell culture gives the ability to study the physiological effects of various stimuli, enhancing our understanding of basic cell biology including the cause and effect relationship. However, cell cultured in this system lacks 3D tissue architecture and does not provide a true resemblance of living tissue. The limited proliferative ability and chances of dedifferentiation during in vitro 2D expansion could possibly hinder the chondrocyte and stem cell-based cartilage tissue engineering. This limitation can be overcome by tissue engineering models. Three-dimensional in vitro cartilage models allow the study of cell-cell and cell-extracellular matrix interactions with addition to the influence of the micro environment on cellular differentiation and proliferation. It simulates normal cell morphology, proliferation, differentiation and migrations, better than the 2D cell culture. Dynamic 3D cultures using scaffolds be it natural or synthetic scaffolds are currently being explored. With continuous research, it is hoped that the employment of 3D cultures will provide promising insight into developing effective strategies and successful intervention in managing cartilage disorders.